Effect of feeding fish meal and rumen protected amino acids on blood parameters of murrah buffalo heifers - Yadav, Dipin Chander (Indian Journal of Dairy Science, 2017)
The present study attempts to analyze the effect of feeding fish meal and rumen protected amino acids on blood biochemical parameters of Murrah buffalo heifers. Eighteen Murrah buffalo heifers between one to two year, on the basis of age and weight randomly distributed into three treatment groups each having six heifers. Animals in treatment T1 (control group), fed with conventional ration, in T2 (fish meal supplementation by replacing conventional concentrate) and in T3 (with 10g commercial bypass Lysine per animal per day + 2g commercial bypass Methionine per animal per day) for 90 days. The amount of concentrate mixture was given to each group in such a way that the experimental ration remains iso-proteinaceous. Blood samples were collected for hemato-biochemical analysis at monthly intervals. Feeding of protected amino acids result in significant increased (P<0.05) in concentration of total protein and albumin and a significant decreased (P<0.05) in concentration of blood urea nitrogen but concentration of other biochemical parameters like plasma glucose, globulin and albumin globulin ratio showed non-significant difference among the treatments.